A π-stacked porphyrin-fullerene electron donor-acceptor conjugate that features a surprising frozen geometry - Ciammaichella, Alina; Dral, Pavlo; Clark, Timothy; Tagliatesta, Pietro; Sekita, Michael; Guldi, Dirk Michael (Chemistry - A European Journal, 2012)
A "frozen" electron donor-acceptor array that bears porphyrin and fullerene units covalently linked through the ortho position of a phenyl ring and the nitrogen of a pyrrolidine ring, respectively, is reported. Electrochemical and photophysical features suggest that the chosen linkage supports both through-space and through-bond interactions. In particular, it has been found that the porphyrin singlet excited state decays within a few picoseconds by means of a photoinduced electron transfer to give the rapid formation of a long-lived charge-separated state. Density functional theory (DFT) calculations show HOMO and LUMO to be localized on the electron-donating porphyrin and the electron-accepting fullerene moiety, respectively, at this level of theory. More specifically, semiempirical molecular orbital (MO) configuration interaction (CI) and unrestricted natural orbital (UNO)-CI methods shed light on the nature of the charge-transfer states and emphasize the importance of the close proximity of donor and acceptor for effective electron transfer. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.